Caracterização de genes de mamona (Ricinus communis L.) Associados a tolerância a estresses abióticos - Gomes Neto, Valdir (2021)
Castor bean (Ricinus communis L.) is an oilseed species globally recognized for an uncounted number of industrial applications and high market value of the oil extracted from its seeds. Besides, it has significant socioeconomic importance concerning its production being traditional and mostly carried out in Brazil by family farmers in the region of the Brazilian Northeastern semiarid region, where rudimentary crops predominate under adverse conditions typical of the region. Therefore, the present study aimed the characterization and overexpression of castor bean genes associated with better tolerance to abiotic stresses during germination and initial seedling development. Three families of genes related to superoxide dismutase (SOD), small heat shock proteins (sHSP), and the nuclear transcription factor Y subunit B (NF-YB) were analyzed, according to the importance of these genes in the literature, and their selection by complementary analysis of within a castor bean microarray for genes expressed under heat stress. The identification and characterization of these families in castor bean was compared with angiosperm genomes, obtaining the profile of gene expression under conditions of abiotic stresses during imbibition, radicle protrusion (germination per se) and post-germination (young seedlings), and functional characterization of the target genes for tolerance to abiotic stresses through overexpression in Arabidopsis thaliana. In CHAPTER 1 (published article), we identified the SOD gene family in castor bean (RcSOD), and the orthologous genes in angiosperms, showing the expression profile of RcSOD genes in embryos during imbibition and germination under different osmotic potentials (water restriction). The RcCuZnSOD1 and RcFeSOD8 genes were induced during imbibition by osmotic stress that induces ‘priming’ in Castor bean seeds as being associated with beneficial responses to seeds and seedlings vigor in different Castor bean genotypes. In CHAPTER 2 (article to be submitted), we identified possible regulatory elements of RcSOD genes under abiotic stresses and regulation by ABA, and the mechanism of regulation by the microRNA 398 for the RcCCuSOD4 and RcCuZnSOD3 genes. We identified the RcCuZnSOD1 and RcFeSOD8 genes as responsive to heat stress (35 °C) during imbibition and germination. Besides, we identified that other RcSOD genes (RcCCuSOD4, RcFeSOD7, RcCuZnSOD3) were induced in seeds under heat stress during radicle protrusion and in seedlings with 2 cm roots. It was possible to observe the subcellular localization of the RcSOD genes in Nicotiana benthamiana leaves, in which RcSOD genes (RcMnSOD5 and RcFeSOD8) may have differences compared to the subcellular location in A. thaliana. In CHAPTER 3 (published article), we initially identified 41 genes of the heat shock protein family predicted in Castor bean (RcsHSP), showing that tandem duplication seems to be one of the possible causes for the largest number of castor genes compared to A. thaliana. Besides, we showed the pattern of XI gene expression of 10 RcsHSP genes induced during radicle protrusion and early seedling stage. However, demonstrating the specificity of expression in roots, cotyledons, and leaves at different stages of seedling development under heat stress. Finally, we performed the functional characterization through the overexpression of two RcsHSP genes (RcsHSP12 and RcsHSP19) in A. thaliana, resulting in (a) higher percentage of seed germination under heat, osmotic and saline stresses; (b) greater enzymatic antioxidant potential of SOD; (c) and higher concentration of protective carbohydrates (sucrose and raffinose). In CHAPTER 4 (submitted article), we identified the family of genes of the nuclear transcription factor subunit B (NF-YB) in Castor bean and made the functional characterization of the RcNF-YB8 gene regarding the induction of early flowering in A. thaliana. The phylogenetic comparison allowed us to identify orthologous genes in angiosperms and motif patterns that may be associated with differences between the RcNF-YB subfamilies. The induction of RcNF-YB genes was observed to be greater during imbibition and germination compared to the postgerminative phase, also showing different profiles of induction and suppression by heat stress. The RcNF-YB8 gene demonstrated suppression by heat stress and a pattern of greater expression in leaves, while the overexpression in A. thaliana also demonstrated to induce early flowering, therefore, impacting the size of the plant and fruits, and consequent productivity. The results involve a broad characterization of genes from three important families in the response of seeds and seedlings to abiotic stresses and subsequent plant development, in which the characterization of the genes showed significant relevance indicating target genes potentially useful in breeding programs towards varieties of Castor bean with superior vigor aimed at better stand stablishment and crop development, and consequently better productivity of Castor bean around the world and by the family farmers in the Brazilian Northeast semiarid.